Handbook of signal processing systems - Deprettere, Ed F.; Leupers, Rainer; Takala, Jarmo; Bhattacharyya, Shuvra S. (Springer New York, 2013)
Handbook of Signal Processing Systems is organized in three parts. The first part motivates representative applications that drive and apply state-of-the art methods for design and implementation of signal processing systems; the second part discusses architectures for implementing these applications; the third part focuses on compilers and simulation tools, describes models of computation and their associated design tools and methodologies. This handbook is an essential tool for professionals in many fields and researchers of all levels.